PERAN GURU DALAM MEMBANGKITKAN MOTIVASI BELAJAR SISWA KELAS TINGGI MADRASAH IBTIDAIYAH NEGERI 1 KOTA TERNATE SELAMA PEMBELAJARAN ONLINE - Kodrat Hi Karim (Universitas Khairun, 2021)
This study aims to describe how the teacher's role in motivating the learning of high grade students at Madarasah Ibtidaiyah Negeri 1 Ternate in Online Learning. Research on the role of teachers in motivating high-class student learning during the pandemic, was carried out at Madrasah Ibtidaiyah Negeri 1 Ternate City, carried out in the even semester of the 2021-2022 academic year. This research method is descriptive qualitative, research subjects are teachers and high grade students, namely class IV, V and class VI at Madrasah Ibtidaiyah Negeri 1 Ternate. To obtain data, researchers used the techniques of observation, Interview, and documentation. Data analysis is done by organizing the data, describing it into units, synthesizing it, compiling it into a pattern, selecting the appropriate data, and drawing conclusions. The results of this study are that there are various efforts made by teachers in generating learning motivation for high grade students of MIN 1 Ternate City during the implementation of online learning, namely (1) providing added value for students who submit assignments on time; (2) giving prizes for students who complete assignments correctly and on time, and (3) preparing various media and learning methods to foster student enjoyment, and (4) giving praise to students who successfully answer questions during learning.